2011
DOI: 10.1007/s10681-011-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation for the rust resistance gene Lr34/Yr18 in Canadian wheat cultivars

Abstract: The wheat (Triticum aestivum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
3
25
3
Order By: Relevance
“…Alleles of resistant (Lr34res-D) and susceptible (Lr34sus-D) cultivars are characterized by only three mutations ). Only five major Lr34 haplotypes, either representing mutated versions of Lr34res-D or variants of Lr34sus-D, were identified in the wheat gene pool (Dakouri et al 2010(Dakouri et al , 2014Lagudah et al 2009;McCallum et al 2012). A recent study of a collection of 252 accessions of the D-genome progenitor of bread wheat, Aegilops tauschii, revealed very low nucleotide variation in Lr34 (π = 0.0011; Krattinger et al 2013), similar to the results presented here for Yr36.…”
Section: Reduced Genetic Diversity At the Wks1 Locussupporting
confidence: 82%
See 1 more Smart Citation
“…Alleles of resistant (Lr34res-D) and susceptible (Lr34sus-D) cultivars are characterized by only three mutations ). Only five major Lr34 haplotypes, either representing mutated versions of Lr34res-D or variants of Lr34sus-D, were identified in the wheat gene pool (Dakouri et al 2010(Dakouri et al , 2014Lagudah et al 2009;McCallum et al 2012). A recent study of a collection of 252 accessions of the D-genome progenitor of bread wheat, Aegilops tauschii, revealed very low nucleotide variation in Lr34 (π = 0.0011; Krattinger et al 2013), similar to the results presented here for Yr36.…”
Section: Reduced Genetic Diversity At the Wks1 Locussupporting
confidence: 82%
“…The characterization of nucleotide diversity of the leaf rust QR gene Lr34 revealed relatively lowsequence diversity. In the wheat gene pool, two predominant Lr34 alleles (Lr34res-D and Lr34sus-D) were found that differ by only two critical codons in exon 11 and exon 12 (Dakouri et al 2010;Krattinger et al 2009Krattinger et al , 2011Lagudah et al 2009;McCallum et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Breeding for resistance to leaf rust started in the late 1930s, when the susceptibility of ‘Thatcher’, which was grown extensively in the western Prairie Provinces from 1939 to 1960, resulted in severe yield and economic losses (McCallum and DePauw , McCallum et al. ). Since then, many resistance genes have been deployed.…”
Section: Biotic Stressesmentioning
confidence: 99%
“…The tyrosine residue at position 634 of LR34sus-D is highly conserved among different ABCG proteins in various plant species (Krattinger et al 2011). Several additional Lr34 alleles have been identified at lower frequencies in the wheat genepool (Dakouri et al 2010;Lagudah et al 2009;McCallum et al 2012). However, none of these were associated with disease resistance and they either represent In this study we examined Lr34 homoeologs and orthologs in a set of wheat, rice and sorghum genotypes.…”
Section: Introductionmentioning
confidence: 99%